2021
DOI: 10.3390/ijerph182312544
|View full text |Cite
|
Sign up to set email alerts
|

User-Centred Design of a Final Results Report for Participants in Multi-Sensor Personal Air Pollution Exposure Monitoring Campaigns

Abstract: Using low-cost portable air quality (AQ) monitoring devices is a growing trend in personal exposure studies, enabling a higher spatio-temporal resolution and identifying acute exposure to high concentrations. Comprehension of the results by participants is not guaranteed in exposure studies. However, information on personal exposure is multiplex, which calls for participant involvement in information design to maximise communication output and comprehension. This study describes and proposes a model of a user-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Reviewing TAD data in this study, in collaboration with the participants, showed a possible error rate of up to 5–10% for each activity. To reduce the probability of human error, different approaches are employed, e.g., user-cantered study design to construct better TADs [ 14 ] and using GPS and other variables as activity identifiers to reduce manual input [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing TAD data in this study, in collaboration with the participants, showed a possible error rate of up to 5–10% for each activity. To reduce the probability of human error, different approaches are employed, e.g., user-cantered study design to construct better TADs [ 14 ] and using GPS and other variables as activity identifiers to reduce manual input [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study used next-generation sensing and monitoring (NGSM) technology—a wearable PM monitor—to determine how these types of devices could provide fine-grained spatiotemporal resolution of personal exposure to PM 10 in a period of persistent ATIs and immediately after, based on individual activities and microlocations. Individual-level exposure assessments were based on data obtained from personal PM monitors (PPM) used as part of the ICARUS H2020 project [ 27 ], where participants carried the devices for one week in a heating and non-heating season, and additionally provided hourly data on their activities, transport mode, and microlocations [ 28 ].…”
Section: Introductionmentioning
confidence: 99%